2021
DOI: 10.3390/s21030933
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Cement Mortars Enhanced with Graphene Nanoplatelets and Carbon Nanotubes

Abstract: Recent findings have brought forward the potential of carbon nano-species, especially nanotubes and graphene, to impart exceptional multifunctional potential to cement, offering simultaneous enhancement of mechanical, fracture mechanical and electrical properties. While available knowledge on the topic is still limited, there is a complete absence of direct comparisons of the potential of the nano-species to improve strength and toughness and provide multifunctionality to the mortars. The study offers a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The underlying mechanism was related to the high surface area and wrinkled morphology of the GNPs, which increased the roughness of the interface between GNPs and the mortar matrix, thus enhancing the cohesive forces of the cement mortar [ 52 , 53 ]. However, when GNPs are over-added, agglomeration tends to occur in the cement matrix, which increases the porosity of the cement composite, thus adversely affecting the strength of the specimen [ 54 ]. It may be the combined role of both; the GNP additive in cement mortar hasn’t indicated significant mechanical properties improvement.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanism was related to the high surface area and wrinkled morphology of the GNPs, which increased the roughness of the interface between GNPs and the mortar matrix, thus enhancing the cohesive forces of the cement mortar [ 52 , 53 ]. However, when GNPs are over-added, agglomeration tends to occur in the cement matrix, which increases the porosity of the cement composite, thus adversely affecting the strength of the specimen [ 54 ]. It may be the combined role of both; the GNP additive in cement mortar hasn’t indicated significant mechanical properties improvement.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive literature review was conducted to gather experimental results regarding the CS of GrNCC. Relevant data from a variety of published articles 16 , 17 , 26 , 28 , 29 , 68 93 that provide thorough insights into the factors and characteristics that affect compressive strength was compiled, resulting in a database comprising 172 data points as depicted in Appendix A. The selective method of data compilation looked to enhance the dataset with high-quality and appropriate information to conduct a thorough analysis of factors influencing compressive strength.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that the optimal point for snow-melting performance was at a depth of 3 cm from the center of the slab. Using thermal imaging, it was confirmed that the ECON slab maintained its overall temperature, even when the outside temperature was −4.2 • C. Cement mortar mixed with CNTs is being explored in various directions in research [18][19][20][21][22]. In addition to the heating performance, previous studies have focused on the electrical performance of cement mortar mixed with CNTs.…”
Section: Introductionmentioning
confidence: 99%